GAGAL JANTUNG KIRI DAN HIPERTENSI PULMONAL - Sargowo, Djanggan (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2017)
In patients with left heart failure, pulmonary hypertension and right ventricular dysfunction is a common condition and has important implications in the development of disease, disability and death, so it required special attention. Pulmonary hypertension is the most common form with approximately 65-80% of cases. Although today is already highly developed understanding of the pathophysiology and clinical assessment, as well as setting the hemodynamic definition and classification of pulmonary hypertension in left heart failure, but the interrelation hemodynamics in pulmonary hypertension combination of pre- and post-capillary is still very complex, and there is no evidence-based recommendations the handling of pulmonary hypertension is left heart failure. Here, we will discuss the prevalence and significance of pulmonary hypertension and cardiac dysfunction Right in patients with both heart failure with ejection fraction decreased, as well as heart failure with ejection fraction, as well as provides an overview of the pathophysiology of the complex due to the interaction of cardiopulmonary left heart failure, which can supports the evolution of the phenotype of the left ventricle into the right ventricle phenotype through the travel history of heart failure. Next, we will discuss fenoitp pulmonary hypertension by combining the clinical context, the assessment of non-invasive and invasive hemodynamic variables in a structured diagnostic assessment.